2016
DOI: 10.1292/jvms.15-0551
|View full text |Cite
|
Sign up to set email alerts
|

Spatial assessment of the potential risk of avian influenza A virus infection in three raptor species in Japan

Abstract: Avian influenza A, a highly pathogenic avian influenza, is a lethal infection in certain species of wild birds, including some endangered species. Raptors are susceptible to avian influenza, and spatial risk assessment of such species may be valuable for conservation planning. We used the maximum entropy approach to generate potential distribution models of three raptor species from presence-only data for the mountain hawk-eagle Nisaetus nipalensis, northern goshawk Accipiter gentilis and peregrine falcon Falc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…While there is limited evidence of disease transmission by migratory birds (McClure, 1974;Kim et al, 2012a;Moriguchi et al, 2016), their role as vectors and transporters of recently identified pathogens is largely unclear (Choi et al, 2015). More research on invasive species, known pathogens and other microorganisms carried by migratory landbirds will increase our knowledge of emerging diseases and protect animal and human health (World Health Organisation, 2017).…”
Section: Gaps In Understanding the Ecosystem Roles Of Migratory Landbmentioning
confidence: 99%
“…While there is limited evidence of disease transmission by migratory birds (McClure, 1974;Kim et al, 2012a;Moriguchi et al, 2016), their role as vectors and transporters of recently identified pathogens is largely unclear (Choi et al, 2015). More research on invasive species, known pathogens and other microorganisms carried by migratory landbirds will increase our knowledge of emerging diseases and protect animal and human health (World Health Organisation, 2017).…”
Section: Gaps In Understanding the Ecosystem Roles Of Migratory Landbmentioning
confidence: 99%
“…To minimize multi‐collinearity of environmental predictor variables, a PCA was carried out (Cruz‐Cárdenas, López‐Mata, Villaseñor, & Ortiz, ; Moriguchi, Onuma, & Goka, ) using SPSS 22.0. We used eigenvalues larger than 1.0 and the scree plot criterion or “broken stick” stopping rule for PCA in item level factoring (Bernstein, Garbin, & Teng, ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the human population density from the Asia Continental Population Datasets (2000-2020), which are publicly and freely available both through the WorldPop Dataverse Repository and the WorldPop project website (http://www.worldpop.org.uk/data/), were used as predictor variables in this research. Principal component analysis (PCA) was used to reduce the number of continuous environmental variables [37,42,43]. During PCA, we used eigenvalues larger than 0.97 and the scree plot criterion for PCA in item level factoring [44].…”
Section: Environmental Variables and Preprocessingmentioning
confidence: 99%